Proses Berpikir Siswa Field Independent (FI)-Field Dependent (FD) dalam Menyelesaikan Soal Matematika di Kelas XII MIPA SMA Negeri 3 Kota Jambi - Simanjuntak, Melati Veronica; Dewi, Sri; Simamora, Risma (Universitas Batanghari Jambi, 2022)
This research is motivated because students' ability to master mathematical concepts cannot be measured only from student learning outcomes, but in students' thinking processes in solving problems. One way can be analyzed through solving math problems. Because, in solving problems it is impossible for students' minds to be exactly the same as other students because each individual has a different thinking style, these differences can be expressed through cognitive styles. The thinking process indicators used in this study are 1) understanding formation 2) opinion formation 3) decision formation 4) drawing conclusions. This type of research is a descriptive qualitative research that aims to describe the thinking process of Field Independent (FI)-Field Dependent (FD) students in solving math problems. This research was conducted in class XII MIPA SMA N 3 Jambi city in the even semester of the 2021/2022 academic year. The method used for data collection in this study is the method of tests and interviews. The main instrument in this study was the researcher himself and other instruments, namely the GEFT test, math test question sheets, and interview guidelines. The results of this study indicate that: 1) Students with the FI cognitive style fulfill all stages of the thinking process well in solving math problems and can develop their own structure on different questions. 2) Students with FD cognitive style can only fulfill the stages of opinion formation and decision formation for questions that have been done frequently and have difficulty solving different questions from before. That way, teachers need to adapt learning to students' cognitive styles and need to train students with questions that improve students' thinking processes.